THE LEGAL DILEMMA OF MANAGING AND REGULATING PRIVATE CONSUMPTION OF CANNABIS IN RELATION TO THE WORKPLACE - S’celo Walter Sibiya (Obiter, 2024)
In South Africa, consumption of cannabis was a criminal offence in past decades. However, in September 2018, the Constitutional Court judgment in the Prince case decriminalised the private consumption of cannabis. Although the judgment was welcomed by many South Africans, including employees, its interpretation and implementation has been marred by legal ambiguity. The Constitutional Court did not prescribe how employers should manage and regulate the private consumption of cannabis in relation to the workplace. In order to maintain workplace safety, a majority of employers have adopted and enforced a zero-tolerance policy on alcohol, drugs and substance abuse. A majority of employers have relied on urinalysis testing to detect cannabis in the workplace. Some employees, after testing positive for cannabis, have been dismissed for contravening their employer’s zero-tolerance policy, without conclusive evidence of impairment. This thorny issue is explored in this article. First, it seeks to examine whether merely testing positive for cannabis is sufficient to prove intoxication that may result in an employee’s impairment. Secondly, the question is whether urinalysis testing precisely determines whether an employee cannot function and perform their duties normally.